2019
DOI: 10.1186/s12978-018-0662-9
|View full text |Cite
|
Sign up to set email alerts
|

An awareness-raising framework for global health networks: lessons learned from a qualitative case study in respectful maternity care

Abstract: BackgroundThe increase in global health networks as mechanisms for improving health and affecting social change has been recognized as a key component of the global health landscape today. To successfully raise awareness of shared causes, global health networks need tools to help them plan successful campaigns and evaluate the impact of their work, as well as to coordinate and reinforce each other’s efforts. One global health network, the Respectful Maternity Care (RMC) Global Council, can be credited with rai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
52
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(62 citation statements)
references
References 23 publications
7
52
2
Order By: Relevance
“…Therefore, further qualitative research is recommended to unravel the reasons behind this finding. As per earlier studies, we also observed that the wealth index is a crucial factor for unmet fertility needs, as unmet needs are lower for the wealthiest quintile households [28][29][30][31]33,38]. A positive association between health and wealth status has been well established, as mothers from the poorest households have limited access to health facilities and mass media; therefore, they are less likely to be informed of the detrimental effect of excess fertility.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Therefore, further qualitative research is recommended to unravel the reasons behind this finding. As per earlier studies, we also observed that the wealth index is a crucial factor for unmet fertility needs, as unmet needs are lower for the wealthiest quintile households [28][29][30][31]33,38]. A positive association between health and wealth status has been well established, as mothers from the poorest households have limited access to health facilities and mass media; therefore, they are less likely to be informed of the detrimental effect of excess fertility.…”
Section: Discussionsupporting
confidence: 79%
“…The use of contraceptive methods is a significant factor of unmet need of fertility desire in our study that is related to religious beliefs [26]. Women often choose to prevent pregnancy by using various contraceptive methods for either have a birth interval or to stop childbearing; however, contraceptive discontinuation is very common in developing countries [30,31,33]. Studies observed that the various reasons for limiting contraceptive use include contraception failure, actual or perceived problems with the contraception method, lack of information, religious conservatism, husband's reluctance, and various supply-side factors (e.g., family planning kit, health education) that strongly contribute to an unplanned pregnancy and unwanted births [8,34].…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…RMC refers to "care organized for and provided to all women in a manner that maintains their dignity, privacy and confidentiality, ensures freedom from harm and mistreatment, and enables informed choice and continuous support during labour and childbirth" [12]. RMC has been measured through systematic labour observations, cross-sectional surveys using standardized questionnaires as well as through in-depth interviews with maternity care providers and postpartum women [8,[13][14][15][16]. In these studies [8,[13][14][15][16], the RMC metrics focus on childbirth experiences in the following domains: physical, verbal, and psychological abuse, discriminatory care, vaginal examinations, companionship, pain relief, choice of alternative birthing position, and health system drivers.…”
Section: Introductionmentioning
confidence: 99%
“…Reviews have shown the effectiveness of mass media campaigns targeted at reducing unhealthy habits or promoting healthy behaviours such as breast feeding or family planning, among others 21–27. However, significant changes in behaviour can be achieved only when campaigns are well designed and carried out at sufficient scale and intensity 21 28–36…”
Section: Introductionmentioning
confidence: 99%